Pengaruh Politik Minoritas di Indonesia dalam Pilpress 2024 (Relevansi Konsep Fairness John Rawls) - Endi, Yohanes; Ranubaya , Fransesco Agnes (Sekolah Tinggi Widya Sasana, 2023)
The focus of this research examines the relevance and implications of John Rawls' concept of fairness in the context of minority politics in Indonesia, especially in the 2024 presidential election. John Rawls, in his A Theory of Justice, proposes the concept of justice as fairness, which is based on two principles: the same basic freedoms for all citizens and fair equality of opportunity. This study analyzes how this concept can be applied to Indonesia's political situation, where ethnic and religious minorities are often marginalized in the political and policy-making process. Through literature analysis and public opinion survey methods, this study evaluates how the 2024 presidential election reflects Rawls' principles of justice, particularly in terms of fair treatment, distribution of opportunities, and inclusion. The findings show that the Prabowo-Gibran presidential ticket received widespread support from various religious groups, including minorities, indicating the potential for inclusivity and acceptance in the context of this election. However, the study also underlines the risk of polarization and discrimination in political campaigns, emphasizing the need to maintain plurality